Restless Legs Syndrome in Psoriasis: A Multicenter Study on Its Prevalence, Severity, and Impact on Patients - Nguyen CTH; Nguyen NHM; Van TT (Clinical, Cosmetic and Investigational Dermatology)
Chuyen Thi Hong Nguyen, Nguyet Huu Minh Nguyen, Trung The Van Department of Dermatology, University of Medicine and Pharmacy at Ho Chi Minh City, 700000, VietnamCorrespondence: Chuyen Thi Hong Nguyen, Department of Dermatology, University of Medicine and Pharmacy at Ho Chi Minh City, 217 Hong Bang Street, Ward 11, District 5, Ho Chi Minh City, Vietnam, Tel +84 28 38566154, Email chuyennguyen@ump.edu.vnPurpose: Psoriasis is a chronic inflammatory skin disease often associated with multiple comorbidities, including restless leg syndrome (RLS). However, the prevalence and impact of RLS on quality of life and clinical outcomes in patients with psoriasis remain underexplored, particularly in Asian populations. In this study, we compared the prevalence of RLS in patients with psoriasis and healthy controls and evaluated the association between RLS and quality of life, sleep disturbances, and clinical severity of psoriasis.Patients and Methods: This multicenter, cross-sectional study involved 212 participants (106 patients with psoriasis and 106 healthy controls) and was conducted from March to July 2024 at three major hospitals in Ho Chi Minh City, Vietnam. RLS was diagnosed according to the International Restless Leg Syndrome Study Group (IRLSSG) criteria. The RLS severity, sleep quality, quality of life, and psoriasis severity were assessed using the Restless Legs Syndrome Rating Scale, Pittsburgh Sleep Quality Index, Dermatology Life Quality Index, and Psoriasis Area and Severity Index (PASI), respectively.Results: The prevalence of RLS was significantly higher in patients with psoriasis than in healthy controls. Patients with psoriasis and RLS exhibited significantly poorer sleep quality and a greater impact on quality of life than those without RLS. The RLS group exhibited a higher PASI score, indicating more severe psoriasis. A strong positive correlation was observed between PASI and RLS severity.Conclusion: RLS is significantly more prevalent in patients with psoriasis and is associated with worse sleep quality, greater impairment of quality of life, and increased psoriasis severity. Early screening for RLS in patients with psoriasis using the IRLSSG criteria may facilitate timely intervention and improve outcomes.Keywords: psoriasis vulgaris, restless legs syndrome, restless legs syndrome study group, Pittsburgh Sleep Quality Index, Dermatology Life Quality Index